Visita Guiada: procedimentos de escuta performativa de si - Andréa Lúcia Sério; Patrícia Natividade de Pinho (Revista do Colóquio, 2020)
Abstract: The article proposes to share poetic processes of the Guided Tour dance performance developed during the eight-year period (2012-2020) with artists from three professional dance companies in Brazil. The processes that gave rise to the procedure named: performative listening to oneself are presented, which are contextualized in theoretical articulation with the notion of performative will, proposed by Eleonora Fabião and with the concept of listening, in the approach of Hubert Godard, in order to rub meanings of individuation and collectivity in the performative experience of bodies, potentially transforming culturally established habits in those environments of dance creation.Keywords: creation; body; performance; dance.
Keywords: Creation; body; performance; dance.; Criation; Body; Performance; Dance